Synthesis and activity of di- or trisubstituted N-(phenoxyalkyl)- or N-{2-[2-(phenoxy)ethoxy]ethyl}piperazine derivatives on the central nervous system. Issue 11 (15th June 2018) - Pańczyk, Katarzyna; Pytka, Karolina; Jakubczyk, Magdalena; Rapacz, Anna; Sałat, Kinga; Furgała, Anna; Siwek, Agata; Głuch-Lutwin, Monika; Gryboś, Anna; Słoczyńska, Karolina; Pękala, Elżbieta; Żmudzki, Paweł; et al.
Graphical abstract: Highlights: Presented compounds possess mainly antagonistic activity for serotonergic receptors. Compound9 showed 5-HT1A Ki  = 5 nM, 5-HT7 Ki  = 70 nM, α1 Ki  = 15 nM, D2 Ki  = 189 nM. Compound9 – anxiolytic-like activity at 2.5 mg/kg and MES ED50  = 26.33 mg/kg (mice, i.p. ). Abstract: Aim of the study was evaluation of anxiolytic, antidepressant, anticonvulsant and analgesic activity in a series of a consistent group of compounds. A series of eleven new N -(phenoxyalkyl)- or N -{2-[2-(phenoxy)ethoxy]ethyl}piperazine derivatives has been obtained. Their affinity towards 5-HT1A, 5-HT2A, 5-HT6, 5-HT7, D2 and α1 receptors has been assessed, and then functional assays were performed. The compounds were evaluated in mice, i.p. for their antidepressant-like (forced swim test), locomotor, anxiolytic-like (four-plate test) activities as well as – at higher doses – for anticonvulsant potential (MES) and neurotoxicity (rotarod). Two compounds (3, 6 ) were also evaluated for their analgesic activity in neuropathic pain models (streptozocin test, oxaliplatin test) and they were found active against allodynia in diabetic neuropathic pain at 30 mg/kg. Among the compounds, anxiolytic-like, anticonvulsant or analgesic activity was observed but antidepressant-like activity was not. One of the two most interesting compounds is 1-{2-[2-(2, 4, 6-trimethylphenoxy)ethoxy]ethyl}-4-(2-methoxyphenyl)piperazine dihydrochloride (9 ), exhibiting anxiolytic and anticonvulsant activity in mice, i.p. 30 min after administration (at 2.5 mg/kg and ED50  = 26.33 mg/kg, respectively), which can be justified by the receptor profile: 5-HT1A Ki  = 5 nM (antagonist), 5-HT7 Ki  = 70 nM, α1 Ki  = 15 nM, D2 Ki  = 189 nM (antagonist). Another interesting compound is 1-[3-(2, 4, 6-trimethylphenoxy)propyl]-4-(4-methoxyphenyl)piperazine dihydrochloride (3 ), exhibiting anxiolytic, anticonvulsant and antiallodynic activity in mice, i.p., 30 min after administration (at 10 mg/kg, ED50  = 23.50 mg/kg, at 30 mg/kg, respectively), which can be related with 5-HT1A weak antagonism (Ki  = 146 nM), or other possible mechanism of action, not evaluated within presented study. Additionally, for the most active compound in the four-plate test (7 ), molecular modeling was performed (docking to receptors 5-HT1A, 5-HT2A, 5-HT7, D2 and α1A ).